The treatment of patients with an unruptured abdominal aortic aneurysm and a concomitant malignancy: short and long-term results : original article - Epple, Jasmin; Lingwal, Neelam; Schmitz-Rixen, Thomas; Böckler, Dittmar; Grundmann, Reinhart T. (Deutsches Ärzteblatt, 2023)
Background: Having cancer adversely effects the outcome of treatment for an unruptured abdominal aortic aneurysm (AAA). - Methods: A retrospective secondary analysis was performed on the basis of anonymized data from AOK, a German nationwide statutory healthinsurance carrier. Data were evaluated from all of the 20 683 patients who underwent either endovascular (EVAR, 15 792) or open surgical (OAR, 4891) treatment for an unruptured AAA in the years 2010-2016. It was determined in each case whether the patient had a known cancer at the time of the procedure to treat AAA. The analysis concerned patient characteristics, periprocedural complications, and survival after the procedure up to 31 December 2018. - Results: 18 222 patients were free of cancer. In accordance with the known 6:1 sex ratio of AAA, 85.3% of the cancer-free patients and 92.8% of those with cancer were men. At the time of their AAA procedure, 1398 had cancer of the intestine (n = 318), lung (n = 301), prostate (n = 380), or bladder or ureter (n = 399). One-year survival after the AAA procedure was 91.5% in cancer-free patients and 84%, 74.4%, 85.8%, and 85.5% in the patients with the respective types of cancer just mentioned. Having cancer was a significant risk factor for periprocedural mortality (OR 1.326, p = 0.041) and for long-term survival (HR 1.515; p < 0.001). - Conclusion: Having cancer is a risk factor for periprocedural mortality and long-term survival in patients undergoing treatment for an unruptured AAA. This implies that the indications for surgery should be considered with care, particularly in patients with lung cancer, whose 5-year survival rate is only 37.2%.